Effect of flattening wheat grain on grinding modes in roller mill - Kharchenko, Yevgen; Sharan, Andrii; Yeremeeva, Olena (My University, 2021)
The flattening process is used to intensify the grinding of grain during varietal milling of wheat, while the optimal gap between the rolls of the ivy system remains uncertain. Materials and methods. Flattening was carried out in a laboratory ivy machine with a roller diameter of 144.0 mm; 68.4 mm and a rotation speed of 14.6 s-1. Grinding of wheat grain was carried out in a roller mill. The length of the rollers is 70 mm; the number of rifts per 1 cm circle of rollers is 6, the slope of the rifts is 12%, the ratio of circular speeds is 1:2, the speed of rotation of the high-speed roller is 3.93 m/s, the diameter of the rollers is 150 mm, the interdependence of the rifts is the back on the back, the angles of exacerbation of the rifts are 35°/70°. The mode of grinding wheat grain in the ivy machine and in the roller mill was determined by sifting the products obtained through a sieve with holes of 1.0 mm. Granulometric analysis of crushed products was determined by sifting on a standard set of sieves with modu. When grinding ivy products in a roller mill, the total yield of intermediate products is nonlinear in nature and can be approximated by the equation of the second degree. The optimal distance between the rollers of the ivy machine is 1.4 mm, provided that small products after flattening were previously isolated from the mixture of the flattened product. The total product of intermediate products after flattening and grinding in the roller mill has a complex nonlinear nature, which did not allow to establish the optimal value of the gap value between the rollers of the ivy system. The total product of intermediate products obtained in total during flattening and grinding is 2.9 % greater than the total product product yield obtained only in the roller mill with small ivy products previously removed. Differential curves are polymodal and have 5 maximums. Integral curves have an S-shaped appearance. When grinding whole grain, the total yield of intermediate products is greater than when grinding flattened grain in a roller mill under the same conditions. When crushing flattened grain, a greater number of large fractions of products are formed due to small ones.In the range of the established optimal clearance between the rolls of the flattening machine, there are no significant differences between the two methods of grinding wheat. Процес плющення застосовується для інтенсифікації подрібнення зерна пшениці при сортових помелах пшениці, при цьому оптимальна величина зазору між вальцями плющильної системи при помелах пшениці в сортове борошно залишається невизначеною. Плющення здійснювали в лабораторному плющильному верстаті із діаметром вальців 144,0 mm; шириною вальців – 68,4 mm та швидкістю обертання 14,6 s-1. Подрібнення зерна пшениці здійснювали у вальцьовому верстаті. Довжина вальців – 70 мм; кількість рифлів на 1 см кола вальців – 6, ухил рифлів – 12%, співвідношення колових швидкостей – 1:2, швидкість обертання швидкохідного вальця – 3,93 м/с, діаметр вальців – 150 мм, взаєморозташування рифлів – спинка по спинці, кути загострення рифлів – 35°/70°. Режим подрібнення зерна пшениці у плющильному верстаті та у вальцьовому верстаті визначали шляхом просіювання отриманих продуктів через сито з отворами 1,0 мм. Гранулометричний аналіз визначали шляхом просіювання на стандартному наборі сит із модулем Δ≈1,21. При подрібненні продуктів плющення у вальцьовому верстаті загальний вихід проміжних продуктів має нелінійний характер і може бути апроксимований рівнянням другої степені. Оптимальна величина відстані між вальцями плющильного верстату становить 1,4 mm за умови, що дрібні продукти після плющення були попередньо виділені із суміші плющеного продукту. Сумарний добуток проміжних продуктів після плющення та подрібнення у вальцьовому верстаті має складний нелінійний характер, який не дозволив встановити оптимальне значення величини зазору між вальцями плющильної системи. Сумарний добуток проміжних продуктів, які отримано сумарно при плющенні та подрібненні більший на 2,9 % ніж сумарний добуток продуктів отриманих лише у вальцьовому верстаті із попередньо видаленими дрібними продуктами плющення. Диференціальні криві є полімодальними і мають 5 максимумів. Інтегральні криві мають S-подібний вид. При подрібненні цілого зерна сумарний вихід проміжних продуктів більший ніж при подрібненні плющеного зерна у вальцьовому верстаті за однакових умов. При подрібненні плющеного зерна утворюється більша кількість крупних фракцій продуктів за рахунок дрібних. В діапазоні встановленого оптимального зазору між вальцями плющильного верстату, значних відмінностей між двома способами подрібнення пшениці не встановлено.
Keywords: вальцьовий верстат; пшениця; плющення зерна; roller machine; wheat; grain flattening; кафедра технології зберігання і переробки зерна